2005
DOI: 10.1111/j.1740-8709.2005.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding peer supporters and a community support group: evaluating their effectiveness

Abstract: Peer support for breastfeeding mothers has often been promoted as a way of increasing rates in communities with low breastfeeding prevalence, where there are few breastfeeding role models and a bottle-feeding culture predominates. This study evaluated the effectiveness of a peer support initiative, which trained peer supporters who then set up a support group, in an area of social and economic deprivation in South Bristol, UK. The effects of training on 6 local women were explored; the combined effect of peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…50,104,105 Whereas supportive networks can be beneficial to mothers, the potentially negative aspects of networks have the potential to act as psychological stressors, causing cognitive, affective, and biological responses thought to increase the risk for poor health. 5 Providers need to assess a mother's social network in order to identify barriers and facilitators for positive behavior and aim to increase support for the mother.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…50,104,105 Whereas supportive networks can be beneficial to mothers, the potentially negative aspects of networks have the potential to act as psychological stressors, causing cognitive, affective, and biological responses thought to increase the risk for poor health. 5 Providers need to assess a mother's social network in order to identify barriers and facilitators for positive behavior and aim to increase support for the mother.…”
Section: Discussionmentioning
confidence: 98%
“…47,48 Several studies have found that problematic social ties are more predictive of depression than is a lack of supportive relationships. 47,49,50 …”
Section: Measuring Social Networkmentioning
confidence: 98%
“…107 In some programmes, peers decided to support each other by getting together informally or working together with participants, even although this was not a requirement of the programme.…”
Section: Component Definitionmentioning
confidence: 99%
“…For example, when exploring cultural beliefs within the Breastfeeding cluster, it was reported that 'the local community had very few breastfeeding role models and a bottle feeding culture predominates'. 107 Authors from the breastfeeding cluster reported that project teams that did not undertake cultural needs assessments came across difficulties during implementation stages. This suggests, in the context of the breastfeeding cluster, cultural needs assessments are an important initial aspect of the design process.…”
mentioning
confidence: 99%
“…It is notable that many of the proposals made were linked to existing evidence of good practice. Other studies have shown that peer supporters combined with a breastfeeding support group are an effective way of increasing breastfeeding prevalence in areas of low continuation (Ingram et al. 2005), but that women may prefer to attend group based peer support as groups may increase their confidence with breastfeeding (Hoddinott et al.…”
Section: Discussionmentioning
confidence: 99%